(untitled) (Docentes 2.0 Journal, 2022)
In the last ten years, several investigations have been published that propose adaptive or personalized learning models or systems based on the study of learning styles, cognitive abilities, or student interaction with learning objects. The objective of this research was to carry out a systematic review of the adaptive learning models or systems proposed during the 2012-2021 period, taking into account authors of Hispanic-American origin. For its realization, the analytical method was used, under the positivist paradigm, with a descriptive quantitative approach supported by meta-analysis and a cross-sectional experimental design. The content analysis methodology was applied based on the guidelines of the Preferred Reporting Items for Systematic reviews and Meta-Analyses declaration for the elaboration of thoughts on a sample of 50 studies selected from different scientific databases that proposed adaptive learning models or systems. Two categories of analysis were used: the object of research and the structure of the proposed approach or model. Like an analytical matrix, a bibliographic matrix was broken and organized the information collected. The results showed that most of the studies have structures based on three components, with artificial intelligence being the most used adaptability technique; likewise, a relative scarcity of studies carried out in Latin America and Spain was observed. It was concluded by mentioning the research niches on adaptive learning applied to Education and a series of suggestions regarding future work.